An insight into the functional alterations in the gut microbiome of healthy adults in response to a multi-strain probiotic intake: a single arm open label trial - Rodenes-Gavidia, Andrea; Lamelas, Araceli; Bloor, Sarah; Hobson, Anthony; Treadway, Sam; Haworth, Jordan; Vijayakumar, Vineetha; Naghibi, Malwina; Day, Richard; Chenoll, Empar (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Probiotic supplements, by definition, provide a benefit to the host, but few studies have investigated the effect of probiotic supplements in healthy adult populations. Purpose: The present, single arm, open label clinical trial, evaluated compositional and functional changes in the fecal microbiome of healthy adults after supplementation with a 14-strain probiotic. Methods: We analysed the effect of a 14-strain probiotic blend (Bacillus subtilis NCIMB 30223, Bifidobacterium bifidum NCIMB 30179, B. breve NCIMB 30180, B. infantis NCIMB 30181, B. longum NCIMB 30182, Lactobacillus helveticus NCIMB 30184, L. delbrueckii subsp. bulgaricus NCIMB 30186, Lacticaseibacillus paracasei NCIMB 30185, Lactiplantibacillus plantarum NCIMB 30187, Lacticaseibacillus rhamnosus NCIMB 30188, L. helveticus NCIMB 30224, Lactobacillus salivarius NCIMB 30225, Lactococcus lactis subsp. lactis NCIMB 30222, and Streptococcus thermophilus NCIMB 30189), on the faecal microbiota of healthy young adults (n=41) in a single arm study. The adults consumed 4 capsules daily of the 14 strain blend(8 billion colony forming units/day) for 8 weeks. Compositional and functional changes in faecal microbiota before and after supplementation were assessed using shotgun metagenomic sequencing. Fasting breath analysis, faecal biochemistry and bowel habits were also assessed. Results: In healthy adult participants, no significant changes to the overall alpha- or beta-diversity was observed after 8 weeks of multi-strain probiotic supplementation. However, in a simplified model that considered only time and individual differences, significant decreases (p < 0.05) in family Odoribacteraceae and Bacteroidaceae abundance and a significant increase (p < 0.05) in genus Megamonas abundance were observed. At a functional level, there were significant changes in functional gene abundance related to several functional pathways, including phenylalanine metabolism, O-antigen nucleotide sugar biosynthesis, bacterial chemotaxis, and flagellar assembly. No significant changes in stool form or frequency, fecal biochemistry, or methane and hydrogen breath tests were observed. Conclusion: In healthy young adults, overall alpha- and beta-diversity did not change in response to probiotic intake even though modest compositional changes at the family and genus level were observed. However, at functional level, results identified changes in gene abundance for several functional pathways.